1991
DOI: 10.1111/j.1471-0307.1991.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying and foaming properties of protein isolates prepared from heated milks

Abstract: Surface activities at the air‐water interface and the emulsifying and foaming properties of sodium caseinate, conventional casein‐whey protein co‐precipitate prepared from milk heated at 90°C × 15 min at pH 6.6 and milk protein isolates prepared from milks heated at 90°C × 15 min at pH 7.5 or at 60°C × 3 min at pH 10.0 were determined. The surface activities of the four proteins at the air‐water interface were similar, while the emulsifying capacity and emulsion stabilizing ability of casein was less than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The low foam stability reported for SC agrees with results of Dalgleish (1997), who stated that SC was less effective when compared to whey proteins in forming a strong lamellar layer between air cells, resulting in a stable foam. Casein foams produced high overruns, with poor stability when compared to egg albumin and whey protein foams (Phillips and others 1990;Grufferty and Mulvihill 1991;Huang and others 1997). When casein adsorbed at the air/ water interface, the hydrophilic portions extended into the solution preventing hydrophilic portions from binding to each other, thus the rigid lamella was not formed (Dalgleish 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low foam stability reported for SC agrees with results of Dalgleish (1997), who stated that SC was less effective when compared to whey proteins in forming a strong lamellar layer between air cells, resulting in a stable foam. Casein foams produced high overruns, with poor stability when compared to egg albumin and whey protein foams (Phillips and others 1990;Grufferty and Mulvihill 1991;Huang and others 1997). When casein adsorbed at the air/ water interface, the hydrophilic portions extended into the solution preventing hydrophilic portions from binding to each other, thus the rigid lamella was not formed (Dalgleish 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy proteins are known as effective foaming and emulsifying agents. Caseins adsorbed well at the air/water and oil/water interface producing foams with high overrun (air incorporation), but less foam when compared to other milk protein isolates (Grufferty and Mulvihill 1991;Euston and others 1995;Dalgleish 1997). When comparing dairy protein foams, whey proteins aggregated at the air/water interface slower and formed smaller air cells than did casein proteins, and whey protein foams were more stable (Cayot and Lorient 1997).…”
Section: P Rotein Solubility In An Aqueous Systemmentioning
confidence: 94%
“…[66]). Furthermore, heat treatment in conditions that favour the formation of small, serum complexes produces isolates with somewhat improved rehydration properties and viscosity, and modified emulsifying and foaming properties as compared with sodium caseinate or conventional milk protein isolate [67,68]. Bohoua-Guichard et al [23] have also reported improved emulsifying properties of model heat-induced protein complexes when both β-lactoglobulin and κ-casein are involved in the complex, rather than either one protein or the other.…”
Section: Implications Of the Complexes In Other Processesmentioning
confidence: 99%
“…BMWPC7.5, 2.5 and4.5 was found to be the most effective at stabilizing the emulsion over a 60 min period, followed by BMCCP, TBMP, BMS, and BMAC (Table 5).Whey proteins form more stable emulsions than caseins (Phillips, 1981) presumably because surface films of whey protein are more viscous than those of caseins (Castle et al, 1987) . The complexed whey protein in BMCCP may be responsible for the greater stability of emulsion prepared from this protein compared to emulsion prepared from BMAC (Grufferty and Mulvihill, 1991) .All samples had higher ES at pH 8 than those at pH 3 and 5. Table (6) illustrates the digestive action of trypsin on buttermilk solids and buttermilk protein preparations during 60 min.…”
Section: Resultsmentioning
confidence: 95%
“…Regarding emulsifying properties of buttermilk casein powders, the results showed that BMCCP had the highest EC, compared with TBMP and ABMC at the pH range studied. This result was attributed to the heat treatment applied during preparation of BMCCP, which induced whey protein complexation with casein and MFGM protein, improves the EC of the resulting isolated protein (Reimerdes and Lorenzen, 1983and Grufferty and Mulvihill, 1991and Kamal, 1998.…”
Section: Resultsmentioning
confidence: 99%